The Viral Effect: A Case Study of Stanley Tumbler on Social Media - Sarjono, Haryadi; Agustina, Dita Michaela; Angeline (Golden Ratio of Data in Summary, 2025)
This article examines the influence of viral video content on social media in shaping marketing performance, sales growth, and brand awareness, using Stanley Tumbler as a case study. Utilizing a qualitative descriptive methodology, the research draws upon secondary data gathered from digital news outlets, social media interactions, and relevant online sources. The analysis highlights how user-generated content particularly on platforms like TikTok functions as a catalyst for brand revitalization and consumer engagement. The Stanley Tumbler phenomenon illustrates how emotionally driven and socially shared content can transform public perception and consumer behavior. Strategic responses from the brand, including promotional campaigns and limited-edition releases, demonstrate the critical role of real-time adaptability in capitalizing on viral trends. Framed within the Uses and Gratifications Theory and Viral Marketing Theory, the study underscores consumers' participatory role in content circulation and brand amplification. Ultimately, the findings suggest that a combination of emotionally resonant narratives and agile, community-centered marketing strategies contributes significantly to sustained brand equity and competitive advantage in the digital marketplace.